Transformasi Gaya Dakwah Islam di Era digital - Zaman, Mujadiduz; Robith Ilman, Mohammad; Maulidi, Ilham (IAIN Madura, 2023)
The purpose of researchers in examining this film is to find out how the transformation of Islamic da'wah occurs with its various elements. This research is descriptive qualitative. Based on the results of research and data analysis obtained that in the digital era, namely since the 1980s until now, dawah elements have undergone rapid transformation both from the aspects of dai, da'wah partners, materials, strategies, and goals. All of them always utilize digital technology, especially in broadcasting Islamic values so that the scope of material can be easily accessed by levels of society. This transformation has the advantage of ease of access, but also has a very basic drawback, namely the refraction of da'wah material that can be accepted by ordinary people, because incompetent preachers deliver material that they do not master.